The Influence of Transformational Leadership Style, Compensation and Work Environment on Employee Loyalty at PT Irfa'i Berkah Sejahtera Kediri - Wulansari, Dewi; Bhirawa, Sigit Wisnu Setya (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim: This study aims to analyze the influence of transformational leadership style, compensation, and work environment on employee loyalty at PT Irfa'i Berkah Sejahtera Kediri. Design/Method/Approach : This investigation uses a descriptive quantitative methodology with a sample of 83 employees who have at least 3 years of experience, this is determined through a purposive sampling approach where data is analyzed using multiple linear regression with SPSS version 23. Research Findings : The results of the study show that transformational leadership styles, compensation, and work environment have a significant influence on employee loyalty. The contribution of these three variables to employee loyalty reached 68%. Theoretical contribution/originality : This study makes a theoretical contribution by combining three important variables in a model that explores employee loyalty in multi-sector companies, as well as providing new information about human resource dynamics. Practitioner/Policy Implications : The results of the study can facilitate companies in increasing their employee loyalty through the implementation of transformative leadership, effective compensation, and a pleasant work environment. Research limitations : This study was conducted at PT Irfa'i Berkah Sejahtera Kediri on employees with a minimum service period of three years, examining the influence of transformational leadership style, compensation, and work environment on employee loyalty.